(untitled) (Revista LIDER, 2020)
The process of adoption of transport technologies based on electricity is understood as a complex framework of technical, economic, regulatory, financial and socio-cultural aspects. The objective of this paper is to identify agents, interests, enrollments and specific socio-technical devices that are deployed within the framework of the adoption process of transport technologies based on electric energy, from a systemic and territorial perspective. It was a descriptive study with a qualitative approach, for which secondary information was reviewed and 21 semi-structured interviews were applied to intentionally selected key informants. It was possible to verify the emergence of at least 3 empirical dimensions, in which the deployment of devices, controversies and socio-technical arrangements can be observed: financial-commercial, public-private policies and regulatory and scientific-technological framework. This led to the conclusion that a socio-technical perspective with a systemic and territorial approach allows us to find new mechanisms of agency that influence the process of technology adoption and also allowed to advance a proposal for a socio-technical model of a systemic nature, with the aim to develop research and intervention at the territorial level, and thus make a contribution to the design and implementation of public policies and private investments against climate change.